2022
DOI: 10.1126/scisignal.abi7400
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic zinc promotes IL-1β production by monocytes and macrophages through mTORC1-induced glycolysis in rheumatoid arthritis

Abstract: Zinc metabolically reprograms monocytes and macrophages to promote inflammation in rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
1
13
1
Order By: Relevance
“…Bioavailable zinc in the monocyte cytoplasm is essential for protein phosphatase 2 phosphatase activator inhibition and mTORC1/p-S6K phosphorylation. Zip8 expression is associated with IL-1b production in monocytes/ macrophages in severe arthritis (104). Immunostaining confirmed that glycogen synthase kinase 3b expression is prevalent in macrophages in the RA-injured synovium, and glycogen synthase kinase 3b inactivation is a metabolic switch that induces mitochondria in macrophages to use oxygen inefficiently to produce sufficient ATP (105).…”
Section: Ramentioning
confidence: 78%
See 2 more Smart Citations
“…Bioavailable zinc in the monocyte cytoplasm is essential for protein phosphatase 2 phosphatase activator inhibition and mTORC1/p-S6K phosphorylation. Zip8 expression is associated with IL-1b production in monocytes/ macrophages in severe arthritis (104). Immunostaining confirmed that glycogen synthase kinase 3b expression is prevalent in macrophages in the RA-injured synovium, and glycogen synthase kinase 3b inactivation is a metabolic switch that induces mitochondria in macrophages to use oxygen inefficiently to produce sufficient ATP (105).…”
Section: Ramentioning
confidence: 78%
“…Both undifferentiated monocytes and macrophages in RA are in a hypermetabolic state (148). IL-1b, which is a consequence of metabolic reprogramming, seems to be a vital contributor to the pathogenesis of RA (102)(103)(104)(105)(106)(107)(108). Cinnamaldehyde inhibits the expression of the succinate receptor 1 and the accumulation of succinate, leading to restricted HIF-1a activation and ultimately limiting glycolytic activity (102).…”
Section: Ramentioning
confidence: 99%
See 1 more Smart Citation
“…As a common pro-inflammatory cytokine, IL-1β is secreted by most innate immunity cells, including neutrophils, monocytes, and macrophages. Once innate immunity cells recognize the pathogens, they would secrete IL-1β to promote inflammatory responses, including the generation of ROS to kill pathogens (34). As a result, the concentration of IL-1β could indicate the body infection.…”
Section: Discussionmentioning
confidence: 99%
“…Zn is second only to iron as the most abundant trace mineral in humans in our body. Research has focused on the utility of this transition metal in the immunologic system (7)(8)(9)(10). It seems that this trace element may boost immune function, soothe glycemia levels, and help keep cardiac, ocular, and cutaneous systems healthy, targeting the T-cell metabolism intimately (11)(12)(13).…”
mentioning
confidence: 99%